Hubungan Pengetahuan dan Sikap Tentang Keselamatan dan Kesehatan Kerja dengan Kejadian Kecelakaan Kerja pada Pekerja di PT. New Saripati Batang Kuis Kecamatan Batang Kuis Kabupaten Deli Serdang - Reni Aprinawaty Sirait (STIKes Santa Elisabeth Medan, 2021)
Introduction : Occupational safety and health factors were very important and must be considered by workers, this was a shared responsibility, there needs cooperation between the government, companies and workers to avoid work related accidents. Method : quantitative research methods that was analytical surveys using a cross-sectional in the processing section of 55 populations with sampling techniques using Total Sampling.Result : The results of the bivariate study showed that there was a relationship between attitude and the incindence of workplace, namely p-value (0,022). Conclusion : Companies improve management in providing supervision and training to workers and made regulations and policies for those who violate sunctions or warnings. Every worker who made a mistake had also been identified with incompetence determined.